DAMPAK PEMBELAJARAN DARING TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Fitri Alfiaturrohmaniah; Siti Masfuah; Mila Roysa (WASIS : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this study is to describe the impact of online learning on the learning outcomes of fourth grade elementary school students.The research method used is qualitative with a descriptive approach. Data was collected by observation, in-depth interviews, and documentation. The research was conducted at SDN 2 Rengging. The research focus is the impact of the online learning process on learning outcomes in science and Indonesian subjects. The research informants were 13 consisting of one fourth grade teacher, six guardians and six students consisting of two high-ability students, two medium-ability students and two low-ability students. The data analysis stage in this study used source triangulation.The results of the study found that in the implementation of online learning at SDN 02 there were positive and negative impacts, but in the learning process at SDN 2 Rengging more highlighted the negative impact, namely students did not understand the material. This happens because the teacher only conveys the material without any direct explanation, the child's lack of motivation to learn, the memory is full, and there are too many assignments.